Regulatory B Cells: Role in Type 1 Diabetes - Boldison, Joanne; Wong, F. Susan (Frontiers in Immunology, 2021)
Regulatory B cells (Bregs) have an anti-inflammatory role and can suppress autoimmunity, by employing both cytokine secretion and cell-contact mediated mechanisms. Numerous Breg subsets have been described and have overlapping phenotypes in terms of their immune expression markers or cytokine production. A hallmark feature of Bregs is the secretion of IL-10, although IL-35 and TGFb-producing B cells have also been identified. To date, few reports have identified an impaired frequency or function of Bregs in individuals with type 1 diabetes; thus our understanding of the role played by these Breg subsets in the pathogenesis of this condition is limited. In this review we will focus on how regulatory B cells are altered in the development of type 1 diabetes, highlighting both frequency and function and discuss both human and animal studies.